Growth performance of weaner lambs maintained on varying levels of dietary protein in pre-weaning phase - Santra, A; Karim, S A (The Indian Journal of Animal Sciences, 2012)
The pre-weaner lambs fed creep mixture with high, medium and low levels of DCP in addition to free suckling and ad lib. cowpea hay were maintained on a composite ration with 50:50 roughage and concentrate in post-weaning phase to study the influence of pre-weaning plane of varying protein levels on post-weaning growth performance of lambs. The birth and weaning weights of male were higher than that of the female lambs while irrespective of levels of protein in creep mixture, the weaning weights were similar in the 3 groups (11.3 kg). Under post-weaning phase, the dry-matter intake, digestibility of dry matter and nutrients and plane of nutrition was similar in the 3 groups while these parameters were higher in male than that in female lambs. All the lambs were in positive nitrogen balance and having 34 % nitrogen retention. The lambs in the 3 groups consumed 85 g DM, 7.9 g DCP and 47.0 g TDN / kg Wâ°Ë™â·âµ /day which amounted to 38.0 g DCP / unit of Mcal DE consumed and had 111.0 g ADG. It is concluded that feeding higher levels of CP in creep mixture was not helpful in boosting growth of post-weaner lambs whereas the DMI, its utilization and growth responses were better in male than female lambs.